Non-Price Rationing of Intermediate Goods in Centrally Planned Economies - Manove, Michael (Econometrica, 1973)
How should rule-of-thumb priorities be assigned for the rationing of intermediate goods in an economy marked by shortages and non-scarcity prices? A method is developed for setting these priorities in an optimal way, and the method is applied to Soviet data as an illustration. 1.